
①解方程:(x+7)(x+5)-(x+1)(x+5)=42 ②解不等式:(3x+4)(3x-4)>9(x-2)(x+3
①解方程:(x+7)(x+5)-(x+1)(x+5)=42②解不等式:(3x+4)(3x-4)>9(x-2)(x+3)...
①解方程:(x+7)(x+5)-(x+1)(x+5)=42 ②解不等式:(3x+4)(3x-4)>9(x-2)(x+3)
展开
1个回答
展开全部
①x2+5x+7x+35-(x2+5x+x+5)=42,
去括号得:x2+5x+7x+35-x2-5x-x-5=42,
移项合并得:6x+30=42,
解得:x=2;
②整理得:9x2-16>9(x2+3x-2x-6),
去括号得:9x2-16>9x2+27x-18x-54,
移项合并得:9x<38,
解得:x<
.
去括号得:x2+5x+7x+35-x2-5x-x-5=42,
移项合并得:6x+30=42,
解得:x=2;
②整理得:9x2-16>9(x2+3x-2x-6),
去括号得:9x2-16>9x2+27x-18x-54,
移项合并得:9x<38,
解得:x<
38 |
9 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询